Matrix Vesicle Mediated Mineralization - A Review - Devika. B1 , K. R. Don2 , V. Vishnu Priya3 , (Indian Journal of Forensic Medicine & Toxicology, 2020)
Teeth are composed of the mineralized tissues dentine and cementum, and a mineralized structure, thedental enamel. The pulp may also mineralize in response to aging processes and/or pathologic aggressions.The process of mineralization is specific for each dental tissue. Matrix vesicles have been implicated inthe mineralisation of calcified cartilage, bone and dentin. It is an orchestrated sequence of ultrastructuraland biochemical events that lead to crystal nucleation and growth. Matrix vesicles appear to mineralize byconcentrating calcium and phosphate at a protected site close to the inner leaflet of the vesicle membrane.Calcium may be attracted by its affinity for acidic phospholipids of the vesicle membrane, and phosphatemay be concentrated by the action of transmembrane phosphatases of the matrix vesicle membrane.Evidence is accumulating to suggest that alkaline phosphatase of the matrix vesicle membrane functionsas a phosphotransferase or phosphate vector, transporting PO4 across the vesicle membrane. The influx ofphosphate ions into the matrix vesicle is mediated by several proteins such as TNAP, ENPP1, Pit1, annexinand so forth. The catalytic activity of ENPP1 generates pyrophosphate (PPi) using extracellular ATPs as asubstrate, and the resultant PPi prevents crystal overgrowth. However, TNAP hydrolyzes PPi into phosphateion monomers, which are then transported into the matrix vesicle through Pit1. Accumulation of Ca2+ andPO43- inside matrix vesicles then induces crystalline nucleation, with calcium phosphate crystals budding offradially, puncturing the matrix vesicle’s membrane and finally growing out of it to form mineralized nodules.Their exact role, if any, in the nucleation of hydroxyapatite mineral, and its association with collagen fibresThe organic Matrix has been debated and is controversial. Several hypotheses have been recently introducedto explain in greater detail how Matrix vesicles function in biomineralization. This review will summariserecent advances, and ultra-structural and biochemical aspects on Matrix vesicles - mediated mineralization.